Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1559-1816.2011.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Name? The Effects of the Labels “Fat” Versus “Overweight” on Weight Bias1

Abstract: This research examined the effects of the labels "fat" vs. "overweight" in the expression of weight bias, with the prediction that the label "fat" biases individuals to respond more negatively than does the label "overweight." In Study 1, participants' attitudes toward people labeled as fat were less favorable than were their attitudes toward people labeled as overweight. In Studies 2 and 3, although participants chose similar-sized figures to depict fat and overweight targets, weight stereotypes and weight at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 42 publications
1
62
0
1
Order By: Relevance
“…For example, the term 'obese' may be perceived as confusing or emotionally charged for some individuals, 23,24 but may motivate weight loss for others. 23 The term 'fat' may be perceived as pejorative and derogatory for some individuals, 25,26 but in certain cases attitudes toward 'fat people' have been found to invoke more favor and less disgust than 'obese people', 27 and certain groups of individuals (for example, members of the Fat Acceptance movement) may publicly embrace this term. 28,29 Thus, weight-related language can invoke different interpretations and individual preferences, and this needs to be better understood especially in the context of health care where patient-provider discussions about weight are routine.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the term 'obese' may be perceived as confusing or emotionally charged for some individuals, 23,24 but may motivate weight loss for others. 23 The term 'fat' may be perceived as pejorative and derogatory for some individuals, 25,26 but in certain cases attitudes toward 'fat people' have been found to invoke more favor and less disgust than 'obese people', 27 and certain groups of individuals (for example, members of the Fat Acceptance movement) may publicly embrace this term. 28,29 Thus, weight-related language can invoke different interpretations and individual preferences, and this needs to be better understood especially in the context of health care where patient-provider discussions about weight are routine.…”
Section: Introductionmentioning
confidence: 99%
“…In their model, they focus on three main psychological coping strategies. The first is attributing negative events to unfair discrimination, which is likely difficult for overweight individuals because weight bias can be more socially acceptable than racism, sexism, and many other forms of bias (Brochu & Esses, 2011;Crandall, Eshleman, & O'Brien, 2002). In fact, Crocker, Cornwell, and Major (1993) provided evidence that overweight individuals do not attribute negative feedback to discrimination.…”
Section: Fighting Against the Cyclementioning
confidence: 97%
“…Indeed, weight stigma has even been described as the last "acceptable" form of bias (Puhl & Brownell, 2001). Overweight individuals are negatively stereotyped, and commonly perceived as lazy, lacking in willpower and control, and unattractive (Brochu & Esses, 2011). Only severe obesity is protected, and only in some cases, by legislation, and so it is not illegal or unlawful for overweight or moderately obese individuals to be denied services or opportunities on the basis of their weight Puhl, Heuer, & Sarda, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vartanian (2010b) found the word obese to evoke greater negative evaluations than fat. However, a study by Brochu and Esses (2011) indicated that the term fat sparks more negativity than overweight. The words obesity, bariatric and overweight are biomedical terms that are currently the most preferred in medical discourses.…”
Section: Weight Stigmamentioning
confidence: 99%